2015
DOI: 10.1021/acs.iecr.5b03707
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Thermophysical Properties of Functionalized Imidazolium Thiocyanate Based Ionic Liquids

Abstract: New cyano-based ionic liquids with thiocyanate anion and nitrile, ally, benzyl, and hydroxyl functionalized imidazolium cations were prepared, and some of their important thermophysical properties were measured. Properties such as density, viscosity, and refractive index were measured over various temperature ranges. From the experimental density values, the molecular volume, standard molar entropy, lattice energy, and thermal expansion coefficient of the ionic liquids were calculated. The thermal stabilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 45 publications
(105 reference statements)
6
30
0
Order By: Relevance
“…For the density measured for 25 mg/ml to 45 mg/ml of ATP concentration, for only 45 mg/ml ATP concentration in water and for pure acetate based ionic liquid from 25°C to 75°C (Table D.1, Table D.2, Table D.3, Table D.4, Table D.5, Table E and Table F), the molecular volume data showed an increase with respect to an increase in temperature. Gonfa, et al, (2015) concluded results over molecular volume similar to our findings.…”
Section: Molecular Volumesupporting
confidence: 91%
See 1 more Smart Citation
“…For the density measured for 25 mg/ml to 45 mg/ml of ATP concentration, for only 45 mg/ml ATP concentration in water and for pure acetate based ionic liquid from 25°C to 75°C (Table D.1, Table D.2, Table D.3, Table D.4, Table D.5, Table E and Table F), the molecular volume data showed an increase with respect to an increase in temperature. Gonfa, et al, (2015) concluded results over molecular volume similar to our findings.…”
Section: Molecular Volumesupporting
confidence: 91%
“…Table B, Table C), the molecular volume data showed an increase with respect to an increase in temperature. Gonfa, et al, (2015) concluded findings over molecular volume similar to our work. …”
Section: Coefficient Of Thermal Expansionsupporting
confidence: 91%
“…Selection of cations from the imidazolium, pyrrolidininium, and ammonium classes along with the thiocyanate anion resulted in fifteen ILs as reported in Table . The preparation of these ILs is well established in literature . The general criterion of dehydrogenation of AB is the disruption of dihydrogen bonding to suppress induction period.…”
Section: Resultsmentioning
confidence: 99%
“…1‐Ethyl‐3‐methylimidazolium thiocyanate ([EMIM][SCN], ≥95% purity), AB (97% purity), and EDAB (96% purity) were purchased from Sigma‐Aldrich. The [EMIM][SCN] was purified using ethyl acetate and diethyl ether and then dried at 48°C at a vacuum of 0.1 pa for 2 days . Later 1 H NMR analysis was performed to check the purity of IL.…”
Section: Methodsmentioning
confidence: 99%
“…ILs show excellent thermal and electrical stability. [6][7][8][9] The knowledge of interactions between ILs and molecular solvents is essential for industry and research [10][11][12] for designing a group of alternative solvents for various applications. Addition of molecular solvents to ILs strongly affects various properties such as density, viscosity, and conductivity.…”
Section: Introductionmentioning
confidence: 99%